Untersuchungen zum geschlechtsspezifischen Verhalten von Seehunden (Phoca vitulina) auf See - Hülse, Sandra (2004)
Most seals (pinnipeds) disperse from centralised terrestrial haul out sites to forage at sea which results in great intraspecific competition for prey. This competition may be reduced by gender-specific differences in depth use, something which should be enhanced by sexual dimorphism because diving ability is a function of body size. This thesis discusses the sex-specific behaviour of harbour seals (Phoca vitulina) in the North Sea. The aim was to determine the extent to which this species might have gender-dependent foraging strategies and, where apparent, to identify possible causes. The diving behaviour of six males and six females was analysed using animal-attatched data loggers (dead reckoners). With a weight of 73 kg (SD = 10) the equipped males were approx. 30 % heavier than females at 55 kg (SD = 8). All seals spent most of their time at sea (males 75.8 %, females 88.1 %) and perfmmed mainly U-shaped dives (ea. 80 %). The maximum recorded dive depth was 43 m for the males and 28 m for the females. Maximum dive duration lasted to 10 minuntes for females and 16 minutes for males. Mean trip duration was 44.1 h (SD = 65.5) for males and 46.8 h for females (SD = 35). Both genders showed significant correlations between dive duration and dive depth, as well as the durations of the descent, bottom and ascent phase and dive depth. However, there were no significant differences either in diving capabilities or in the foraging efficiency of the two sexes. An effect of body size on the diving capabilities of the seals could not been demonstrated. This indicates that the seals' diving capabilities in the North Sea are mainly determined by the bathymetry. Possible sex-specific differences might not be revealed because the seals do not reach their physiological limits in the shallow North Sea. Also, the large variance in the data as well as the small sample size mad it difficult to identify gender-specific differences. Tests of statistical power reveal that data from a total of 262 seals would be needed as an adequate ...